1979
DOI: 10.1128/aem.38.3.514-520.1979
|View full text |Cite
|
Sign up to set email alerts
|

Microbial conversion of ethylbenzene to 1-phenethanol and acetophenone by Nocardia tartaricans ATCC 31190

Abstract: A culture of Nocardia tartaricans ATCC 31190 was capable of catalyzing the conversion of ethylbenzene to 1-phenethanol and acetophenone while growing in a shake flask culture with hexadecane as the source of carbon and energy. This subterminal oxidative reaction with ethylbenzene appears not to have been previously reported for Nocardia species. When N. tartaricans was grown on glucose as its source of carbon and energy and ethylbenzene was added, no subsequent production of 1-phenethanol or acetophenone was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Acetophenones were selected for their commercial availability and generally low toxicity in eukaryotic cells. In addition, several acetophenones are natural products (11) or are catabolized by micro‐organisms, thus they are inherently involved in biological systems (12,13). For example, in a study examining acetophenones for activity against mycobacteria, cytotoxicity was observed against three eukaryotic cell lines (14).…”
Section: Sar Of Acetophenonesmentioning
confidence: 99%
“…Acetophenones were selected for their commercial availability and generally low toxicity in eukaryotic cells. In addition, several acetophenones are natural products (11) or are catabolized by micro‐organisms, thus they are inherently involved in biological systems (12,13). For example, in a study examining acetophenones for activity against mycobacteria, cytotoxicity was observed against three eukaryotic cell lines (14).…”
Section: Sar Of Acetophenonesmentioning
confidence: 99%
“…The use of microbial batch fermentations for the production of specific chemicals is often faster, more economical, and cleaner than chemical synthesis. This has been demonstrated in the production of amino acids (7,13,15) and other chemicals (2,4,5,9,14). We previously reported that Streptomyces viridosporus T7A produces a nonspecific aromatic aldehyde oxidase which catalyzes the oxidation of a variety of aromatic aldehydes to their corresponding carboxylic acids with equimolar uptake, of 02 and production of H202 (3).…”
mentioning
confidence: 98%